Waltzing Through Europe Attitudes towards Couple Dances in the Long Nineteenth-Century - Bakka, Egil; Buckland, Theresa Jill; Saarikoski, Helena; Von Bibra Wharton, Anne (Open Book Publishers, 2020)
"From 'folk devils' to ballroom dancers, Waltzing Through Europe explores the changing reception of fashionable couple dances in Europe from the eighteenth century onwards. A refreshing intervention in dance studies, this book brings together elements of historiography, cultural memory, folklore, and dance across comparatively narrow but markedly heterogeneous localities. Rooted in investigations of often newly discovered primary sources, the essays afford many opportunities to compare sociocultural and political reactions to the arrival and practice of popular rotating couple dances, such as the Waltz and the Polka. Leading contributors provide a transnational and affective lens onto strikingly diverse topics, ranging from the evolution of romantic couple dances in Croatia, and Strauss's visits to Hamburg and Altona in the 1830s, to dance as a tool of cultural preservation and expression in twentieth-century Finland. Waltzing Through Europe creates openings for fresh collaborations in dance historiography and cultural history across fields and genres. It is essential reading for researchers of dance in central and northern Europe, while also appealing to the general reader who wants to learn more about the vibrant histories of these familiar dance forms. Discourses We Live By approaches these questions through narrative research, in a process that uses words, images, activities or artefacts to ask people - either individually or collectively within social groupings - to examine, discuss, portray or otherwise make public their place in the world, their sense of belonging to (and identity within) the physical and cultural space they inhabit. This book is a rich and multifaceted collection of twenty-eight chapters that use varied lenses to examine the discourses that shape people's lives. The contributors are themselves from many backgrounds - different academic disciplines within the humanities and social sciences, diverse professional practices and a range of countries and cultures. They represent a broad spectrum of age, status and outlook, and variously apply their research methods - but share a common interest in people, their lives, thoughts and actions. Gathering such eclectic experiences as those of student-teachers in Kenya, a released prisoner in Denmark, academics in Colombia, a group of migrants learning English, and gambling addiction support-workers in Italy, alongside more mainstream educational themes, the book presents a fascinating array of insights. Discourses We Live By will be essential reading for adult educators and practitioners, those involved with educational and professional practice, narrative researchers, and many sociologists. It will appeal to all who want to know how narratives shape the way we live and the way we talk about our lives."